Gender-specific reference values of dynamometric and non-dynamometric trunk performance in individuals with different body fat percentages: A preliminary study - Tangri, Shiksha; Goyal, Kanu; Goyal, Manu; Wanjari, Mayur (Narra J, 2024)
Trunk muscles maintain steady effort with adequate strength and endurance. When the muscle performance is subpar, it might cause lower back discomfort. No reference for trunk strength and endurance has been established previously. The aim of this study was to determine the normative reference values for dynamometric and non-dynamometric tests in people with various body fat percentages. Two hundred sixty-four participants aged 19–40 years old were recruited in this cross-sectional study. The Siri equation was used to calculate the individuals body fat proportions, which were divided into normal, high, and very high body fat for men and women. The Modified Sorenson's and the Back-Leg-Chest Dynamometric tests were utilized to measure muscular performance. The means of strength in females with normal, high, and very high body fat percentages were 27.39, 25.75, and 25.37 N/m2, respectively. The males in the same category had the means of 56.48, 51.79, and 60.17 N/m2, respectively. The highest mean of endurance in females was in those with normal body fat percentage (42.28), so did males (71.02). Our findingssuggest that males had higher trunk muscle strength and endurance than females, and normal-body-fat individuals had the greatest endurance regardless of gender.